Pengukuran Produktivitas dengan Metode APC (American Productivity Center) dan Green Manufacturing di PK Rosella Baru - Rahmawati, Annisa Dinda; Widjajati, Endang Pudji (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to analyze the level of productivity at PK Rosella Baru and provide suggestions for improvements to the company to increase productivity. The method used in this research is quantitative and interviews with data analysis consisting of company data including production numbers, workforce and energy use, scientific articles and other relevant documents. The findings from the research are three outputs, namely productivity levels, profitability and price improvements for company evaluation. Factors that influence this success include the amount of output each year that is in line with the company's targets, a workforce that masters their field, the raw materials and energy used are optimal and a supportive work environment. Recommendations for further research are to analyze how the level of productivity in the industry affects the profitability obtained.